Fe3O4 encapsulated mesoporous silica nanospheres with tunable size and large void pore - Liu, T.; Liu, L.; Liu, Jian; Liu, Shaomin; Qiao, S. (Gaodeng Jiaoyu Chubanshe, 2014)
Magnetic Fe3O4 and mesoporous silica core-shell nanospheres with tunable size from 110–800 nm were synthesized via a one step self-assembly method. The morphological, structural, textural, and magnetic properties were well-characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, N2 adsorption-desorption and magnetometer. These nanocomposites, which possess high surface area, large pore volume and well-defined pore size, exhibit two dimensional hexagonal (P6mm) mesostructures. Interestingly, magnetic core and mesoporous silica shell nanocomposites with large void pore (20 nm) on the shell were generated by increasing the ratio of ethanol/water. Additionally, the obtained nanocomposites combined magnetization response and large void pore, implying the possibility of applications in drug/gene targeting delivery. The cell internalization capacity of NH2-functionalized nanocomposites in the case of cancer cells (HeLa cells) was exemplified to demonstrate their nano-medicine application.